THE CONSTRUCTION OF STUDENTS’ LEARNING MOTIVATION THROUGH AUGMENTED REALITY: A CONSTRUCTIVIST PERSPECTIVE OF JEAN PIAGET IN FIFTH GRADE AT SDN SIDOKERTO 1 - Lutfiyah, Adelia; Fitra Raharja, Hawwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the construction of students’ learning motivation through the use of Augmented Reality (AR) within the framework of Jean Piaget’s constructivist theory in a fifth-grade classroom at SDN Sidokerto 1. The research addresses the limited student engagement and low motivation commonly found in teacher-centered instructional practices, particularly in science learning involving abstract concepts such as food chains. A mixed methods approach with a sequential explanatory design was employed, combining quantitative analysis of pre-test and post-test motivation scores with qualitative interpretation of students’ learning behaviors. The quantitative data were obtained from 20 students using a validated Likert-scale questionnaire, and analyzed using descriptive statistics, Shapiro–Wilk normality test, and paired sample t-test. The results revealed a significant increase in the mean motivation score from 61.68 (pre-test) to 80.15 (post-test), with a gain of 18.47 points. The t-test indicated a statistically significant difference (p < 0.05), and the effect size analysis showed that AR contributed 29% to the improvement of learning motivation, categorized as a moderate effect. Qualitative findings supported these results, indicating increased student engagement, curiosity, and participation during AR-based learning. From a constructivist perspective, the improvement in motivation is explained through the processes of assimilation and accommodation, facilitated by interactive and concrete learning experiences provided by AR. The findings suggest that AR is not merely a technological tool, but a pedagogical medium that supports cognitive construction and enhances intrinsic motivation. Therefore, the integration of AR, aligned with students’ cognitive development, can create meaningful and engaging learning experiences that significantly improve students’ learning motivation.